2010
DOI: 10.1158/0008-5472.can-09-2205
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cationic Channel TRPV2 in Promoting Prostate Cancer Migration and Progression to Androgen Resistance

Abstract: Castration resistance in prostate cancer (PCa) constitutes an advanced, aggressive disease with poor prognosis, associated with uncontrolled cell proliferation, resistance to apoptosis, and enhanced invasive potential. The molecular mechanisms involved in the transition of PCa to castration resistance are obscure. Here, we report that the nonselective cationic channel transient receptor potential vanilloid 2 (TRPV2) is a distinctive feature of castration-resistant PCa. TRPV2 transcript levels were higher in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
180
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(188 citation statements)
references
References 38 publications
6
180
1
Order By: Relevance
“…Invasive cells are reported to secrete proteolytic enzymes known as MMPs, such as MMP-2 and MMP-9, that degrade the basement membrane, which is mainly made up of type IV collagen (27,28). Elevated [Ca 2+ ] i is likely to be involved in the above mechanism since the constitutive activity of TRPV2, another TRP channel, reportedly increases the intracellular Ca 2+ level and promotes prostate cancer-cell invasion through MMP-9 activation (29). The present finding that menthol increases the gelatinase activity of MMP-9 while RQ suppresses it suggests that TRPM8-stimulation positively regulates MMP-9 activity, an inference in line with the TRPM8-induced increase in metastatic potential.…”
Section: Discussionmentioning
confidence: 99%
“…Invasive cells are reported to secrete proteolytic enzymes known as MMPs, such as MMP-2 and MMP-9, that degrade the basement membrane, which is mainly made up of type IV collagen (27,28). Elevated [Ca 2+ ] i is likely to be involved in the above mechanism since the constitutive activity of TRPV2, another TRP channel, reportedly increases the intracellular Ca 2+ level and promotes prostate cancer-cell invasion through MMP-9 activation (29). The present finding that menthol increases the gelatinase activity of MMP-9 while RQ suppresses it suggests that TRPM8-stimulation positively regulates MMP-9 activity, an inference in line with the TRPM8-induced increase in metastatic potential.…”
Section: Discussionmentioning
confidence: 99%
“…However, TRPV2 mRNA or immunoreactivity has also been detected in the brain, autonomic ganglia, spinal cord, skeletal and vascular myocytes, visceral organs (including the intestine, pancreas, spleen, and bladder), and blood cells (Caterina et al, 1999;Ichikawa and Sugimoto, 2001;Muraki et al, 2003;Kashiba et al, 2004;Lewinter et al, 2004;Inada et al, 2006;Lewinter et al, 2008;Hisanaga et al, 2009;Zanou et al, 2009;Link et al, 2010). TRPV2 expression may also be involved in the migration and proliferation of cancer cells (Caprodossi et al, 2008;Monet et al, 2010), and TRPV2-positive neurons observed in the rat myenteric plexus may be IPANs (Kashiba et al, 2004). Mechanosensitivity of TRPV2 was first reported in cardiac myocytes (Muraki et al, 2003), and we have recently reported its expression and mechanosensitivity in developing sensory and motor neurons (Shibasaki et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The biotinylation studies as well as calcium imaging experiments in some works suggest its expression on the plasma membrane (Monet et al, 2009;Monet et al, 2010). It translocates from the cytoplasm to the plasma membrane upon ligand stimulation.…”
Section: Localisationmentioning
confidence: 99%
“…TRPV2 transcript levels are higher in patients with metastatic cancer (stage M1) compared with primary solid tumors (stages T2a and T2b). TRPV2 channel is expressed in PC3 and DU-145 cell lines derived from bone and brain metastasis, respectively (Monet et al, 2009;Monet et al, 2010). TRPV2 protein is expressed in human hepatoblastoma (HepG2) cells (Vriens et al, 2004).…”
Section: Expressionmentioning
confidence: 99%
See 1 more Smart Citation